Preorganizing linear (self-complementary) quadruple hydrogen-bonding arrays using intramolecular hydrogen bonding as the sole force - Prabhakaran, Panchami; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2005)
In this article we describe a rational approach for prefixing multiple cooperative binding sites in an ideal spatial arrangement on a structurally rigid backbone, constrained exclusively by intramolecular hydrogen bonding. The idea is exemplified by the ability of the self-assembling constructs la-e and 2a,b to form hydrogen-bonded dimers, whose structural preorganization has been solely effected by intramolecular hydrogen bonding. The readily accessible amidinourea backbone has been used as a common platform for the construction of a variety of such self-assembling systems. ESI mass spectrometry and single-crystal X-ray diffraction studies have been particularly effective in investigating the self-assembling propensities of these systems. Remarkably, most the H-bonded dimers reported herein undergo an unusual mode of self-assembly, using intermolecular four-membered ring hydrogen-bonded interaction, affording extended supramolecular networks.

Pyrazole-tethered heteroditopic ligands and their transition metal complexes: synthesis, structure, and reactivity - Mukherjee, Anuradha; Subramanyam, U.; Puranik, Vedavati G.; Mohandas, T. P.; Sarkar, A. (European Journal of Inorganic Chemistry, 2005)
Various pyrazole-based PN (2a-c) and N,N (3a-b) ligands have been synthesized. Using representative ligands, Ni-II, Co-II, Cu-II, and Cu-I complexes have been prepared and structurally characterized by crystallography. During complexation of Co-II and Cu-II salts, the phosphane part of the PN ligand oxidized to phosphane oxide. For N,N donor ligands, a dimeric chloro-bridged Ni-III complex was obtained. Ni-II complex 4 is an active catalyst for ethylene oligomerization. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheirn, Germany, 2005).
Keywords: cobalt; Copper; hemilabile ligands; Nickel; oligomerization; Pyrazole

Practical formal synthesis of D-(+)-biotin from 4-formylazetidin-2-one - Kale, Ajaykumar S.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synthesis-Stuttgart, 2007)
A practical synthesis of (3S,6R)-1,3-dibenzyltetrahydro-1H-furo[3,4-d]imidazole-2,4-dione, an important intermediate in the synthesis of biotin, from 4-formyl-3-mesyloxyazetidin-2-one has been achieved. Acid-catalyzed azetidin-2-one ring opening followed by a one-pot conversion of diamine hydrochloride to a cyclic urea and hydroxymethylene to chloromethylene by triphosgene to obtain (4S,5R)-methyl-1,3-dibenzyl-5-chloromethyl-2-oxoimidazolidine-4-carboxyl ate is the key step in this synthesis.
Keywords: azetidin-2-one; beta-Lactams; cyclization; Lactone; reduction

Potential plasmid-curing agent, 8-epidiosbulbin E acetate, from dioscorea bulbifera L. against multidrug-resistant bacteria - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Puranik, Vedavati G.; Rojatkar, Supada; Dhakephalkar, Prashant K.; Shitole, M. G. (International Journal of Antimicrobial Agents, 2008)
Bioassay-guided fractionation of an aqueous methanolic extract of Dioscorea bulbifera L. bulbs was performed using organic solvents. A novel plasmid-curing compound was identified as 8-epidiosbulbin E acetate (EEA) (norditerpene) on the basis of modern spectroscopic analysis and X-ray crystallography. EEA exhibited broad-spectrum plasmid-curing activity against multidrug-resistant (MDR) bacteria, including vancomycin-resistant enterococci. EEA cured antibiotic resistance plasmids (R-plasmids) from clinical isolates of Enterococcus faecalis, Escherichia coli, Shigella sonnei and Pseudomonas aeruginosa with 12-48% curing efficiency. The reference plasmids of Bacillus subtilis (pUB110), E. coli (RP4), P. aeruginosa (RIP64) and Salmonella typhi (R136) were cured with efficiency ranging from 16% to 64%. EEA-mediated R-plasmid curing decreased the minimal inhibitory concentration of antibiotics against MDR bacteria, thus making antibiotic treatment more effective. The antibiotic resistance pattern revealed that the compound was effective in the reversal of bacterial resistance to various antibiotics. In addition, the compound did not show any cytotoxicity against a broad range of human cancer cell lines, namely MCF-7 (breast cancer), SiHa (cervical cancer) and A431 (epidermal carcinoma), and hence has the potential to be used as a lead compound for drug discovery programmes. (C) 2008 Elsevier B. V. and the International Society of Chemotherapy. All rights reserved.
Keywords: 8-Epidiosbulbin E acetate; Antibiotic resistance; Dioscorea bulbifera; Plasmid curing

Phytochemical investigation of artemisia pallens - Ruikar, Anjali D.; Jadhav, Ravindra B.; Phalgune, Usha D.; Rojatkar, Supada R.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Helvetica Chimica Acta, 2011)
Two new eudesmanolides, pallensin (1) and 4-epipallensin (2), along with a known eudesmanolide, santonin, and a known flavone, 4-epivalgarin, have been isolated from the aerial part of A. pallens. Their structures were established by detailed spectral studies (1D and 2D) and by comparison of their spectroscopic data with those of known compounds.

Phyllocladane diterpenes from anisomeles heyneana - Kulkarni, Roshan R.; Shurpali, Ketaki; Gawade, Rupesh L.; Sarkar, Dhiman; Puranik, Vedavati G.; Joshi, Swati P. (Journal of Asian Natural Products Research, 2012)
New phyllocladane diterpene, phyllocladan-16 alpha,17-dihydroxy-19-oic acid (1), together with known phyllocladane diterpene, phyllocladan-16 alpha,19-diol (2), cembrane diterpene ovatodiolide (3), sitosteryl-3-O-beta-D-glucoside (4), and verbascoside (5), were isolated from aerial parts of Anisomeles heyneana. The structure of compound 1 was elucidated by 1D and 2D NMR analyses which included HSQC, HMBC, and nuclear overhauser effect spectroscopy (NOESY) experiments as well as X-ray crystallography. This is the first report of phyllocladane diterpenes from genus Anisomeles. Compounds 1, 3, 4, and 5 were evaluated for inhibition of Mycobacterium tuberculosis and 3 was found to exhibit anti-mycobacterial activity with IC90 6.53 mu g/ml. Compounds 1, 3, and 5, at 100 mu g/ml, were also evaluated for inhibition of Thp-1 cell lines, and compounds 1 and 3 showed 59.02% and 96.4% inhibitions, respectively.
Keywords: Anisomeles heyneana; Lamiaceae; Mycobacterium tuberculosis; phyllocladane diterpenes

Probing the folding induction ability of orthanilic acid in peptides: some observations - Roy, Arup; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (RSC Advances, 2014)
This paper describes the ability of orthanilic acid (2-aminobenzenesulfonic acid, (S)Ant) to promote folding when introduced in a peptide sequence. Three peptide sequences, containing orthanilic acid (SAnt) with a sulfonamide moiety in the turn segment, have been synthesized in the solution phase using suitable coupling agents, and their structural aspects investigated using NMR and X-ray crystallographic studies. Solid- and solution-state conformational analyses reveal that the peptide sequences containing orthanilic acid in their backbone exist in a folded conformation featuring long-range 15-membered ring H-bonding.